Literary Psychology: Main Character Analysis of "The Feisty Fiancee" by Jessica Steele: Psikologi Sastra: Analisis Karakter Utama dalam Novel "The Feisty Fiancee" oleh Jessica Steele - Mariana, Ana (ELOQUENCE : Journal of Foreign Language, 2023)
Background: The emergence of literary psychology studies is inseparable from the link between psychology and literature, so the main character in a literary work in the form of a novel is interesting to analyze. Purpose: This research aims to describe the character types and their changes played by "Yancie Dawkins" and Thompson Wakefield in the novel "The Feisty Fiancee" by Jessica Steele. Method: This research is literature research with a literary psychology approach. The primary data source is a novel entitled "The Feisty Fiancee" by Jessica Steele. Data collection techniques were carried out with manuscript documentation, namely reading the novel's narrative critically and in-depth, reading the storyline continuously, and coding and identifying the text of the story played by the main and supporting actors. The research instrument uses four aspects of the novel, namely; 1) plot, 2) setting, 3) theme, and 4) point of view. While in the aspect of literary psychology, the researcher used the instrument of Flat, Static, and Rounded characters. The data analysis technique is done by content analysis, with five stages, namely identifying the intrinsic elements of the novel, classifying the data, describing the story and dialogue, describing the events that lead to the discussion of the main character, and concluding the subject matter about the types of characters in the main character in the review of literary psychology. Results and Discussion: Yancie Dawkins, is the main character in Julia Steele's The Feisty Fiancée. Steele describes Yancie's physical appearance as a girl who is beautiful, independent, unique, and categorized as a feminist who has a good nature as a female character in real life today. Yancie's type is categorized into Static Character which is hard and annoying Yancie has a stable character from the beginning of the story to the end which is characterized by her stability in facing problems in her life. The supporting character in this novel is played by Thompson, he is a minor character, because Thompson plays an important role in the development of the story, especially the problems faced by Yancie Dawkins. Thompson's type is categorized as a Dynamic Character, constantly changing and developing as the story progresses. Dynamic characters respond to events and experience changes in attitude or outlook. Conclusion and Implications: The conclusion of this study shows that the novel "The Feisty Fiancée" introduces readers to the types of characters that can be emulated in everyday life. However, readers can also understand the roles and changes of characters that can change, according to the conditions of time, place, and events. The implication of the research can be a reference for future researchers to analyze the character and characterization of the characters.